Hadith #4485 - Sahih al-Bukhari - Um Ruman (Sahih al-Bukhari)
Who was `Aisha’s mother: While I was with `Aisha, `Aisha got fever, whereupon the Prophet (ﷺ) said, “Probably her fever is caused by the story related by the people (about her).” I said, “Yes.” Then `Aisha sat up and said, “My example and your example is similar to that of Jacob and his sons:–‘Nay, but your minds have made up a tale. So (for me) patience is most fitting. It is Allah (alone) Whose help can be sought against that which you assert.’ (12.18)
Grade: Sahih

Hadith #4545 - Sahih al-Bukhari - Um Ruman (Sahih al-Bukhari)
Aisha’s mother, When `Aisha was accused, she fell down Unconscious.
Grade: Sahih